2011
DOI: 10.1016/j.ygeno.2010.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Segmentation of genomic and transcriptomic microarrays data reveals major correlation between DNA copy number aberrations and gene–loci expression

Abstract: DNA copy number aberrations (CNAs) are genetic alterations common in cancer cells. Their transcriptional consequences are still poorly understood. Based on the fact that DNA copy number (CN) is highly correlated with the genomic position, we have applied a segmentation algorithm to gene expression (GE) to explore its relation with CN. We have found a strong correlation between segmented CN (sCN) and segmented GE (sGE), corroborating that CNAs have clear effects on genome-wide expression. We have found out that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…Interestingly, recent evidence suggests that these pathways are deregulated in multiple sporadic cancers (Beroukhim et al , 2010). Iodine-131-related changes in tumour tissue may result not only from epigenetic changes but also from copy number alterations (Kang et al , 2006), shown to shape cancerous transcriptome (Ortiz-Estevez et al , 2011). This idea finds some support in that AUTS2 gene located within 7q11.22–7q11.23 region, previously found to be amplified in post-Chernobyl tumours (13), showed a suggestive dose dependency in the tumour tissue based on 2 d.f.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent evidence suggests that these pathways are deregulated in multiple sporadic cancers (Beroukhim et al , 2010). Iodine-131-related changes in tumour tissue may result not only from epigenetic changes but also from copy number alterations (Kang et al , 2006), shown to shape cancerous transcriptome (Ortiz-Estevez et al , 2011). This idea finds some support in that AUTS2 gene located within 7q11.22–7q11.23 region, previously found to be amplified in post-Chernobyl tumours (13), showed a suggestive dose dependency in the tumour tissue based on 2 d.f.…”
Section: Discussionmentioning
confidence: 99%
“…As a distinctive element from other integrative approaches we do not consider only SNPs or genes individually. We take into account the gene loci following the strategy described in [11], that is based on the application of the same smoothing and segmentation algorithm to CN and GE in order to establish comparable regions. Once we get the smoothed segments, we perform two independent analyses for each gene loci: a signal correlation analysis and an alteration frequency analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Our method takes into account the genomic loci, both in the copy number (CN) analysis and also in the gene expression (GE) analysis, and applies the segmentation step proposed by Ortiz-Estevez et al . [11]. These authors designed a method for robust comparison between CN and GE using paired samples.…”
Section: Introductionmentioning
confidence: 99%
“…The matched transcriptomics data is then examined to see if a gene's altered copy number is associated with a concurrent change in the gene's expression [2][17], thus adding weight to the argument that the gene may be contributing to the type of cancer in question [18]. A number of algorithms and bioinformatics tools have been published to aid this type of study [17], [19][23]. Matched data sets have also been used for cancer subtype stratification [21], [24]–[26].…”
Section: Introductionmentioning
confidence: 99%